Pengurangan Arus Inrush Pada Tranformator Daya Dengan Menggunakan Konverter Raktor Dc - Fahrul Rhozi; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The transformer is the main element that is very important in the distribution of electricity. The fault that occurs in the transformer can blocked the process of distribution electrical energy to consumers. And one of them is the emergence of inrush currents when energizing the transformer is one phenomenon that occurs in electric power and affects differential relay performance. In operating a differential relay sometimes it is a fault which causes the protected transformer to trip despite the fact that the transformer is normal. This study proposes Reducing Inrush Current on the Garuda Sakti Substation Power Transformer, to reduce the inrush current in the power transformer when the power transformer is first turned on. The method used in this study is to use a bridge diode type DC reactor which is simulated using Matlab / Simulink software. By connecting in series with each phase of the power transformer. The simulation results the reduction value of inrush current on power transformer 1 with a difference that is at phase R = 29.7 A phase S = -10 A and phase T = -17.5 A. In power 3 transformer at phase R = 32.7 A , phase S = -11.5 A and phase T = -21.9 A. The result of the reduction in inrush current using the DC reactor is compared with the inrush current value. The result of this reduction in inrush current can reduce the inrush current on power 1 transformer at R phase 14.7%, phase S 5.7% and phase T 9.8%. In power transformer 3 it can reduce to phase R 14.5%, phase S 5.9% and phase T 10.8%Keywords : Inrush Current, Power Transformer, DC Reactor